Insights into the structure and inhibition of Giardia intestinalis arginine deiminase: homology modeling, docking, and molecular dynamics studies. Issue 4 (2nd April 2016) - Trejo-Soto, Pedro Josué; Aguayo-Ortiz, Rodrigo; Yépez-Mulia, Lilián; Hernández-Campos, Alicia; Medina-Franco, José Luis; Castillo, Rafael
Abstract : Giardia intestinalis arginine deiminase ( GiADI ) is an important metabolic enzyme involved in the energy production and defense of this protozoan parasite. The lack of this enzyme in the human host makes GiADI an attractive target for drug design against G. intestinalis . One approach in the design of inhibitors of GiADI could be computer-assisted studies of its crystal structure, such as docking; however, the required crystallographic structure of the enzyme still remains unresolved. Because of its relevance, in this work, we present a three-dimensional structure of GiADI obtained from its amino acid sequence using the homology modeling approximation. Furthermore, we present an approximation of the most stable dimeric structure of GiADI identified through molecular dynamics simulation studies. An in silico analysis of druggability using the structure of GiADI was carried out in order to know if it is a good target for design and optimization of selective inhibitors. Potential GiADI inhibitors were identified by docking of a set of 3196 commercial and 19 in - house benzimidazole derivatives, and molecular dynamics simulation studies were used to evaluate the stability of the ligand–enzyme complexes.